Development of a pulsed bremsstrahlung source on a base of a nanosecond and microsecond REB accelerators - Batrakov, A.B.; Egorov, A.M.; Gaponenko, N.I.; Glushko, E.G.; Lonin, Yu.F.; Rudnev, N.I.; Sereda, B.V.; Neklyudov, I.M.; Parkhomenko, A.A.; Grivo, A.G.; Mazilov, A.V. (Вопросы атомной науки и техники, 2004)
In the paper the preliminary results on measuring parameters of a pulsed bremsstrahlung source developed for investigation of physical-mechanical properties of reactor materials are given. Generation of γ-radiation with parameters γ ∼ 0.4...1.0 MeV was carried out at microsecond and nanosecond high-current REB accelerators. The absolute values of an absorbed dose are determined for both nanosecond and microsecond sources of γ-radiation.